Atoms, Bits, and Wits: A New Economics for the Twenty-First Century—Part II. Issue 1 (2nd January 2016) - Jennings, Frederic Beach
Abstract : Learning also affects the organization of economic activity as a "force locomotif" of growth. Bounded rationality opens a theory of planning horizons as an ordinal measure of wits. The realm of wits shines a novel light on the nature of interdependence, since the balance of substitution and complementarity is horizonal: longer and broader horizons shift this balance away from substitution in favor of complementarity, augmenting concerts of interest over conflicts in social relations. Atoms, bits, and wits are modeled to show why substitution only applies to short-run atoms; a case for complementarity rises from both increasing returns and bits, where wits strengthen the case for cooperation as efficient. With complementarity, competition—not collusion—stifles output. The social and institutional implications of this are addressed theoretically in this paper.